2006
DOI: 10.1016/j.virol.2006.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in human cytomegalovirus cytoplasmic assembly sites in the absence of UL97 kinase activity

Abstract: Studies of human cytomegalovirus (HCMV) UL97 kinase deletion mutant (DeltaUL97) indicated a multi-step role for this kinase in early and late phases of the viral life cycle, namely, in DNA replication, capsid maturation and nuclear egress. Here, we addressed its possible involvement in cytoplasmic steps of HCMV assembly. Using the DeltaUL97 and the UL97 kinase inhibitor NGIC-I, we demonstrate that the absence of UL97 kinase activity results in a modified subcellular distribution of the viral structural protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
52
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 42 publications
8
52
0
Order By: Relevance
“…Marschall, unpublished data). Additional cytoplasmic functions of pUL97 (Kawaguchi et al, 1999;Prichard et al, 2005;Azzeh et al, 2006;Romaker et al, 2006) suggest a complex regulation system of pUL97 intracellular transport. Here, we investigated transiently expressed wild-type pUL97 in comparison to the two individually expressed large and small isoforms of pUL97.…”
Section: Results and Discussion Pul97 Occurs In Two Isoformsmentioning
confidence: 99%
“…Marschall, unpublished data). Additional cytoplasmic functions of pUL97 (Kawaguchi et al, 1999;Prichard et al, 2005;Azzeh et al, 2006;Romaker et al, 2006) suggest a complex regulation system of pUL97 intracellular transport. Here, we investigated transiently expressed wild-type pUL97 in comparison to the two individually expressed large and small isoforms of pUL97.…”
Section: Results and Discussion Pul97 Occurs In Two Isoformsmentioning
confidence: 99%
“…Interestingly, the function of UL97 in promoting replication during infection with clinical strains largely depends on the presence of UL135. Further, UL97 mutant viruses exhibit defects in the late stages of virus maturation, producing a number of empty virions and defects in secondary envelopment (55)(56)(57)(58). The similarities in phenotypes associated with the loss of UL135 or UL97 and the interplay between UL135 and UL97 during infection that these phenotypes suggest are intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to RV-VM1, where pp65 was exclusively located in the nucleus and no cytoplasmic aggregates were found. Azzeh et al (2006) showed that infection of HFF with a pUL97-deletion mutant or inhibition of pUL97 in wt-HCMVinfected cells by NGIC-I (non-glyosidic indolocarbazole I) resulted in a reorganization of cytoplasmic assembly sites, including a redistribution of the late protein pp28 and the formation of 2-8 mm wide vacuoles. We observed neither the formation of vacuoles in the cytoplasm nor the redistribution of pp28 after infection with RV-VM1 (not shown).…”
mentioning
confidence: 99%